The gardener of children’s literature (Eurasian Journal of Philology Science and Education, 2016)
The spiritual heritage of the akyn Kairat Zhumagaliyev who takes a special place in the Kazakh poetry, especially in the Kazakh children’s literature is analyzed in the article. On the example of his verses we see the aspiration of children to learn the world around; they reveal the inner world of the child. Many verses of the poet are a direct proof of depth of his judgments about children. Reading Kairat Zhumagaliyev’s verses, it is possible to notice how views and feelings of the child which differ in availability, laconism, and a flexible rhythm change. The poet creates them with love to children whom he very much appreciates. Each verse is in its own way unique and original, bears a huge charge of benefit. Kairat Zhumagaliyev renewed the interest in song lullabies which transmitted peculiarities and originality of folklore. The paper proves that in the Kazakh family mutual understanding and respect between close people, parents and children is one of features of the Kazakh mentality. Verses of the poet are very easy to memorize, they develop memory and oral speech of children.
Keywords: children’s literature; song lullabies; fiction features; internal rhymes; Kazakh poetry; language of the poet.